Asteroseismology of KIC 7107778: a binary comprising almost identical subgiants. Issue 1 (29th January 2018) - Li, Yaguang; Bedding, Timothy R; Li, Tanda; Bi, Shaolan; Murphy, Simon J; Corsaro, Enrico; Chen, Li; Tian, Zhijia
Abstract: We analyse an asteroseismic binary system: KIC 7107778, a non-eclipsing, unresolved target, with solar-like oscillations in both components. We used Kepler short cadence time series spanning nearly 2 yr to obtain the power spectrum. Oscillation mode parameters were determined using Bayesian inference and a nested sampling Monte Carlo algorithm with the diamonds package. The power profiles of the two components fully overlap, indicating their close similarity. We modelled the two stars with mesa and calculated oscillation frequencies with gyre . Stellar fundamental parameters (mass, radius, and age) were estimated by grid modelling with atmospheric parameters and the oscillation frequencies of l = 0, 2 modes as constraints. Most l = 1 mixed modes were identified with models searched using a bisection method. Stellar parameters for the two sub-giant stars are M A = 1.42 ± 0.06 M⊙, M B = 1.39 ± 0.03 M⊙, R A = 2.93 ± 0.05 R⊙, R B = 2.76 ± 0.04 R⊙, t A = 3.32 ± 0.54 Gyr and t B = 3.51 ± 0.33 Gyr. The mass difference of the system is ∼1 per cent. The results confirm their simultaneous birth and evolution, as is expected from binary formation. KIC 7107778 comprises almost identical twins, and is the first asteroseismic sub-giant binary to be detected.